Contemporary performance/technology. - Birringer, Johannes (Theatre Journal)
Examines the integration of computer technologies in dance performances. Transition of gestures in the performing arts; Use of videodance and photographic innovations in motion studies; Projection of moving images using digital technologies; Impact of technological media on contemporary performances; Evolution of media use in artwork productions.